2013
DOI: 10.1155/2013/424651
|View full text |Cite
|
Sign up to set email alerts
|

Methylcobalamin: A Potential Vitamin of Pain Killer

Abstract: Methylcobalamin (MeCbl), the activated form of vitamin B12, has been used to treat some nutritional diseases and other diseases in clinic, such as Alzheimer's disease and rheumatoid arthritis. As an auxiliary agent, it exerts neuronal protection by promoting regeneration of injured nerves and antagonizing glutamate-induced neurotoxicity. Recently several lines of evidence demonstrated that MeCbl may have potential analgesic effects in experimental and clinical studies. For example, MeCbl alleviated pain behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 27 publications
3
61
0
14
Order By: Relevance
“…Vitamin B 12 intake has recently been shown to be correlated with reduction in pain levels in a number of medical conditions, including neuropathy [26]. While neuropathy is not caused by MS, manifestations of MS in the CNS are similar to the damage to the peripheral nervous system seen in neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin B 12 intake has recently been shown to be correlated with reduction in pain levels in a number of medical conditions, including neuropathy [26]. While neuropathy is not caused by MS, manifestations of MS in the CNS are similar to the damage to the peripheral nervous system seen in neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] Saat ini belum terdapat penelitian mengenai pencampuran mekobalamin dengan sediaan parenteral lainnya. Pada observasi terjadi 9 pencampuran sediaan mekobalamin, yaitu dalam ringer laktat 500 cc (3 sediaan), dalam 300 cc ringer laktat (1 sediaan), dan dalam 500 cc ringer laktat (5 sediaan).…”
unclassified
“…One of the main causes for nerve pain, numbness, tingling, and chronic neuropathy is deficiencies in Vitamin B12 and B6; therefore, supplementing with B-vitamins could alleviate many of the symptoms associated with peripheral neuropathy. Vitamin B12 supplementation has been used to treat many diseases, as well as improve memory, and act has a neuronal protection including promoting injured nerves and axonal regeneration (Zhang et al 2013). It has also been shown to have possible analgesic effects on neuropathic pain in clinical studies (Tankaka 2013).…”
Section: B Vitamins: B6 B9 B12mentioning
confidence: 99%
“…It has also been shown to have possible analgesic effects on neuropathic pain in clinical studies (Tankaka 2013). In animal studies, it has been demonstrated that that Vitamin B12 can extenuate nerve damage caused by neuropathy by activating a chemical signal, which helps nerves to regenerate (Zhang et al 2013). In clinical studies, the combination of Vitamin B12, B9 andB6 (methylcobalmin, folic acid and pyridoxal) have been found to improve symptoms and maintain the health of nerves in the extremities as well as treat neuropathic symptoms (Fratoni et al 2015).…”
Section: B Vitamins: B6 B9 B12mentioning
confidence: 99%